The effect of strength shoes on muscle activity during quiet standing - Frank, K.; Baratta, R. V.; Solomonow, M.; Shilstone, M.; Riche, K. (Journal of Applied Biomechanics, 2000)
The goal of this work was to study the effect of Strength Shoes on the activity of leg and postural muscles to gain insight into the mechanisms by which the shoes may improve athletic performance. Surface EMG signals were obtained from the tibialis anterior, medial gastrocnemius, rectus femoris, biceps femoris, gluteus maximus, and erector spinae of 18 healthy athletic subjects. The subjects stood quietly while wearing either normal athletic shoes or Strength Shoes. EMG root mean square value was compared in each muscle using trimmed paired t tests. Significant (p < .002) increases in EMG activity were found in the MG, TA, GM, and ES muscles when the subjects were wearing Strength Shoes as compared to normal shoes. These changes served to stiffen the ankle, counteracting the dorsiflexion moment created by the shoes, and to support an anterior leaning posture, which compensates for the anterior shift in center of pressure. No significant changes were detected in the activities of RF or BF muscles. Using Strength Shoes increased activity in the triceps surae complex and in other muscles mat support the changes in postural requirements caused by the anterior shift in center of pressure.